2009
DOI: 10.1007/s00167-009-0875-0
|View full text |Cite
|
Sign up to set email alerts
|

Tensile forces on sutures in the human lateral knee meniscus

Abstract: Tensile strength is the most often reported parameter in biomechanical investigations of meniscal repair techniques. However, the magnitude of the tensile forces that actually occur on repaired lesions is not clear. The purpose of this study was to investigate if tensile forces occur on repaired lateral meniscal lesions, which could exceed the failure strength of common repair techniques. In human knees (n = 6), vertical-longitudinal lesions 25 mm in length were created in the posterior horn of the lateral men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Uniaxial tension tests are used for evaluation of meniscal attachment function after transplantation [27], tensile forces are used to evaluate suture function in meniscus repair techniques [28,29]. The ball indention test characterizes the viscoelastic properties of meniscal tissue including stiffness, residual force and compression behavior [9,30] and we chose this test also in our biomechanical setup as the cyclic testing mimics physiological loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Uniaxial tension tests are used for evaluation of meniscal attachment function after transplantation [27], tensile forces are used to evaluate suture function in meniscus repair techniques [28,29]. The ball indention test characterizes the viscoelastic properties of meniscal tissue including stiffness, residual force and compression behavior [9,30] and we chose this test also in our biomechanical setup as the cyclic testing mimics physiological loading conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the adhesive strengths of our glues were lower than those of Dermabond ® , they do have clinical relevance. It has been shown that distraction forces acting on a torn meniscus in a cadaver knee model did not exceed 5–10 N when a load of 300 N was applied to the proximal end of the femoral part . Application of the force in such manner allowed to approximate the mean body weight less the weight of the leg itself in the setting of bipedal stance or squatting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that distraction forces acting on a torn meniscus in a cadaver knee model did not exceed 5-10 N when a load of 300 N was applied to the proximal end of the femoral part. 26,27 Application of the force in such manner allowed to approximate the mean body weight less the weight of the leg itself in the setting of bipedal stance or squatting. This means that the stress was not >50-100 kPa, during the recovery period after surgery the load on the knee might be even lower.…”
Section: Discussionmentioning
confidence: 99%
“…The adhesive strength of the adhesive compositions (3.2–3.7 N) should be sufficient to hold the torn meniscus together during the period of healing, as it has been reported that in a cadaver knee model the distraction forces acting on a torn meniscus do not exceed 5–10 N when a load of 300 N is applied [21, 22]. During the recovery period after surgery, the load on the knee would be even lower.…”
Section: Discussionmentioning
confidence: 99%